Cost:Benefit analysis of insect net use in cabbage in real farming conditions among smallholder farmers in Benin. (December 2015) - Vidogbéna, Faustin; Adégbidi, Anselme; Assogba-Komlan, Françoise; Martin, Thibaud; Ngouajio, Mathieu; Simon, Serge; Tossou, Rigobert; Parrot, Laurent
Abstract: Insect net use provides a physical exclusion of pests as well as a microclimate change, thus increasing soil humidity, vegetable quality and yields in tropical conditions. This paper presents the findings of a cost:benefit analysis of this technology in real farming conditions compared to current insecticide practices. The surveys were conducted in Benin for cabbage production ( Brassica oleracea L.) during two production cycles. There were almost no significant differences in costs between unnetted and netted cabbage for the two production cycles. The only factors that varied were farm gate prices, the number of cabbages marketed and their size. Improved yields contributed significantly to the higher cost:benefit ratio for netting protection. Insecticide costs significantly declined by 68%–95% when shifting from unnetted protection to netted protection and total operational and labor costs declined by 3%–40%. Insect net use generated threefold higher margins and an average 1:2.66 cost:benefit ratio compared to 1:1.58 for current practices. Overall, the netting technology displayed less variation for costs, yield, and cabbage quality than insecticides. The next step is to scale up the supply of marketed insect nets. Highlights: Cost:benefit analysis compared insect nets and conventional insecticide use. Cost:benefit ratios ranged from 1:1.93 to 1:2.87 for insect nets. Cost:benefit ratios for current insecticide practices ranged from 1:0.99 to 1:2.77. Insect nets are an attractive option for cabbage production in Africa. Accounting for current farming practices is necessary for cost:benefit analyses.